Conservation of the internal quality of eggs using a biodegradable coating - Oliveira, Gabriel da Silva (2020)
This study aimed to evaluate the effect of a pectin biofilm on the preservation of refrigerated and unrefrigerated eggs during 5 wk of storage based on egg weight loss, albumen height, Haugh unit (HU), and the yolk index (YI). A total of 1,200 nonfertile eggs from GLK Bankiva laying hens (40 wk of age), which were freshly laid and came from a single collection, were obtained from a model poultry rearing system (Planaltina, Federal District, Brazil) that meets all animal welfare criteria. The experimental outline was entirely randomized, with 20 treatments in a factorial scheme of 2 × 2 × 5, with 2 biofilm treatments (with and without) × 2 storage temperatures (refrigeration: 5°C and ambient: 25°C) × 5 storage periods (7, 14, 21, 28, and 35 d), with 12 repetitions per treatment. Starting from the third storage week, increased weight loss (%) was observed in noncoated eggs (4.46 ± 1.06; 5.61 ± 1.37; 6.93 ± 1.66%) compared with biofilm-coated eggs (3.57 ± 1.26; 4.74 ± 1.8; 6.05 ± 2.21%), respectively. The HU variation in the pectin-coated eggs (86.84–78.02) was smaller than that in the noncoated eggs (83.01–64.36) between the beginning (7 d) and the end (35 d) of the experimental period. Eggs with and without biofilm stored in the refrigerator presented average HU values of 91.26 ± 6.27 and 88.35 ± 6.96, respectively. In contrast, when kept at room temperature, eggs with the coating presented higher HU values (71.27 ± 10.78) than eggs without the coating (59.11 ± 15.97). Coated eggs (0.37 ± 0.16) showed higher YI values than noncoated eggs (0.35 ± 0.16). A pectin-based biofilm effectively maintained egg quality during the 35 d of storage.